Assessing nutritional status using dietary patterns from rural nepali women. - Marino-Costello, Elizabeth. (Tufts University. Tisch Library., 2018)
This poster assesses the nutritional status of Nepali women by creating a dietary pattern analysis on those of child-bearing age.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy